Exploring the impact of possession-based performance indicators on goal scoring in elite football leagues - Kapsalis, M.; Plakias, S.; Kyranoudis, A.; Zarkadoula, A.; Lathoura, A.; Tsatalas, T. (Journal of Physical Education and Sport, 2023)
Background Performance analysis has garnered significant attention in recent years, both in research and its practical implementations on the field. A substantial portion of performance analysis revolves around performance indicators.